Study of Black Cotton Soil Characteristics with Molasses - S. Vinodhkumar; Kulanthaivel, P.; Kabilan, A.; Lokeshkanna, K. M. (Asian Journal of Engineering and Applied Technology, 2018)
Civil engineering structure resting on expansive soil needs more attention since it causes undesirable engineering behavior when the soil comes in contact with water. The areas consisting of expansive soil need a proper stabilization method to solve the site problems faced by the civil engineers. Pavements constructed on such soil shows signs of damage continuously during the service life of the pavement eventually increase the maintenance costs. Stabilization of this soil is a usual practice for improving the strength. In this work an attempt was made on the utilization of Molasses with soil by adding various percentages of 5, 7.5, 10, 12.5 and 15% in soil and accessed their geotechnical behavior for different curing periods. The effects of Molasses treatment on the strength improvement of compacted expansive clays are studied based on Unconfined Compression tests for different curing periods of 0, 7 and 14 days. UCS performed on these mixes and identified that addition of Molasses attained high strength with the increasing percent of Molasses in soil. From the test results, it was observed that the UCS peak value were increases to 160%. From the experimental study, it is observed that the treatment of the expansive soil with the addition of Industrial waste material Molasses is more efficient in subgrade modification and other geotechnical applications.